Carbon dot material with whitening and antibacterial functions and application thereof
The carbon dot materials VBL-CDs synthesized by hydrothermal method, combined with the fluorescent whitening agent VBL and other precursor materials, solve the water solubility and light stability of the fluorescent whitening agent in the textile field, and achieve efficient whitening of the fabric and Antibacterial effects provide new textile treatment agent applications.
Patent Information
- Application Number
- CN202411050746.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The application of existing fluorescent whitening agents in the textile field is limited by their poor water solubility and light stability, and lack of antibacterial functions, making them unable to effectively whiten and antibacterial.
A multifunctional carbon dot material VBL-CDs was synthesized by hydrothermal method, and carbon with strong fluorescent brightness, excellent optical properties and antibacterial properties were prepared using precursor materials such as fluorescent whitening agent VBL, citric acid, copper chloride, etc. to prepare carbon with strong fluorescence brightness, excellent optical properties and antibacterial properties. Point material for fabric whitening and antibacterial.
VBL-CDs show efficient whitening and brightening effects on fabrics, and have high antibacterial activity on Gram-positive and negative bacteria, and have good biocompatibility and anti-ultraviolet properties, which provides replacement for traditional fluorescent whitening agents. New application ideas.
Smart Images

Figure CN119118105A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano functional materials, and in particular relates to a carbon dot material with both whitening and antibacterial functions and an application thereof. Background Art
[0002] Cotton fabrics, whether natural or synthetic, are not completely white. Since ancient times, people have been trying to eliminate the yellowish color of white fabrics and visually improve the whiteness and brightness of products. Fluorescent brighteners are products commonly used in the textile field to whiten and brighten fabrics; and in daily life, fluorescent brighteners are also often included in commercial detergent formulas to improve whiteness and enhance the color of fabrics. In addition, fluorescent brighteners are also widely used in coatings, plastics, paper and other fields due to their whitening and brightening functions. However, due to the poor water solubility and light stability of fluorescent brighteners, their commercial application is limited.
[0003] Carbon dots are a type of ultra-small zero-dimensional nanomaterial with a size less than 10 nm. Due to their excellent optical properties, outstanding biocompatibility, attractive catalytic performance, ultra-small size, low toxicity and environmental friendliness, carbon dots have been widely used in biomedicine, sensing, catalysis, optoelectronic devices, lubrication and other fields. However, there is no report on the use of carbon dots as fluorescent whitening agents in the prior art. Summary of the invention
[0004] One of the purposes of the present invention is to provide a carbon dot material having both whitening and antibacterial functions.
[0005] A second object of the present invention is to provide a fluorescent whitening agent comprising the above-mentioned carbon dot material.
[0006] The third object of the present invention is to provide applications of the above-mentioned carbon dot materials.
[0007] To achieve the above objectives, the present invention adopts the following technical solutions.
[0008] A carbon dot material with both whitening and antibacterial functions is characterized in that it is synthesized by a hydrothermal method using a fluorescent whitening agent VBL, citric acid, cupric chloride, ammonia water, ethylenediamine and water as raw materials.
[0009] The molecular formula of the fluorescent brightener VBL is C 36 H 34 N 12 O8S2Na2, CAS number is 12224-16-7.
[0010] The present invention uses fluorescent whitening agent VBL, citric acid and copper chloride as precursors for hydrothermal synthesis to obtain a multifunctional carbon dot material VBL-CDs; specifically:
[0011] ① The carbon dot material VBL-CDs of the present invention has a fluorescence absorption and emission spectrum similar to that of the fluorescent brightener VBL (hereinafter referred to as VBL), can emit blue fluorescence, and exhibits better optical properties than VBL, such as strong fluorescence brightness and excellent fluorescence stability;
[0012] ② The present invention, through clever precursor selection, enables VBL-CDs to have antibacterial properties that ordinary fluorescent whitening agent VBL does not have, and has a highly effective antibacterial effect on both Gram-positive bacteria and Gram-negative bacteria;
[0013] ③Based on the characteristics of carbon dots, VBL-CDs also have good biocompatibility and show good water solubility that VBL does not have.
[0014] Preferably, the mass ratio of the solid raw materials fluorescent whitening agent VBL, citric acid and cupric chloride is 2-3:7-9:1; the volume ratio of the liquid raw materials ammonia water, ethylenediamine and water is 45-55:45-55:1.
[0015] Preferably, the ratio of the solid raw material to the liquid raw material is 230-260 mg:1 mL, that is, the mass volume ratio of the material to the liquid in the reaction system is 230-260 mg:1 mL.
[0016] Preferably, the reaction temperature of the hydrothermal method is 180-200° C., and the reaction time is 2-5 h.
[0017] Furthermore, the product synthesized by the hydrothermal method is post-treated to obtain VBL-CDs. The post-treatment steps are: adding ultrapure water to the product synthesized by the hydrothermal method, and ultrasonicating for 30 minutes; dialysis purification of the solution obtained after ultrasonication, and then freeze-drying to obtain a green powder, namely VBL-CDs.
[0018] The present invention has no specific limitation on the amount of ultrapure water added to the above product; as a specific implementation manner, the amount of ultrapure water added is equal to or slightly larger than the volume of the product.
[0019] Furthermore, the dialysis purification is to dialyze the solution obtained after ultrasound for 4 to 10 hours using a dialysis bag with a molecular weight cutoff of 500 to 3000 Da and ultrapure water, and the ultrapure water is replaced every 1 to 3 hours during the dialysis process.
[0020] The present invention also provides a fluorescent whitening agent comprising the carbon dot material VBL-CDs, which can effectively whiten and brighten fabrics and provide antibacterial properties.
[0021] The present invention also provides the use of the carbon dot material VBL-CDs or the fluorescent whitening agent in preparing a fabric detergent or fabric care agent with whitening and brightening effects.
[0022] The present invention also provides the use of the carbon dot material VBL-CDs or the fluorescent whitening agent in the preparation of an antibacterial fabric detergent or fabric care agent; the antibacterial agent includes Gram-positive bacteria and Gram-negative bacteria.
[0023] Preferably, the amount of the carbon dot material VBL-CDs is 0.25-1.0% (owf), more preferably 0.5% (owf).
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The carbon dot material VBL-CDs of the present invention can emit blue fluorescence and has strong fluorescence brightness and excellent fluorescence stability; therefore, after VBL-CDs are embedded in the fabric surface, due to its high fluorescence intensity and fluorescence stability, VBL-CDs show high efficiency and excellent durability comparable to VBL in whitening and brightening.
[0026] The invention enables VBL-CDs to have efficient antibacterial properties through clever precursor selection; the in vitro antibacterial results show that VBL-CDs has excellent antibacterial activity against both Gram-positive and Gram-negative bacteria, and the fabrics treated with VBL-CDs also have effective antibacterial ability, with the antibacterial rates against Staphylococcus aureus and Escherichia coli reaching 98% and 99% respectively.
[0027] In addition, the experiments also show that the fabric treated with the carbon dot material VBL-CDs of the present invention has good biocompatibility and exhibits satisfactory performance in terms of UV resistance.
[0028] The carbon dot material VBL-CDs of the present invention can achieve efficient whitening and brightening and antibacterial effects after being applied to fabrics, and can provide new ideas for replacing existing fluorescent whitening agents in the field of textiles. Therefore, the carbon dot material VBL-CDs of the present invention can also be used in the preparation of fabric detergents and fabric care agents with whitening and / or antibacterial effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 In the figure, a is the UV-visible absorption spectrum of VBL and VBL-CDs; b is the normalized fluorescence emission spectrum of VBL and VBL-CDs; c is the fluorescence emission spectrum of VBL-CDs in aqueous solution at different excitation wavelengths.
[0030] Figure 2 Comparison of fluorescence intensity of VBL-CDs and VBL at the same concentration (0.1 mg / mL).
[0031] Figure 3a and b are the fluorescence emission changes of VBL and VBL-CDs after irradiation at 365 nm, respectively, and c is the TR emission attenuation point and relative best fitting curve of VBL-CDs and VBL.
[0032] Figure 4 This is a comparison chart of the whiteness values of untreated cotton fabric, VBL-treated cotton fabric, VBL-CDs-treated cotton fabric, and negative control group CDs-treated cotton fabric.
[0033] Figure 5 In the figure a is the fluorescence intensity change spectrum of cotton fabric treated with VBL under ultraviolet irradiation, b is the fluorescence intensity change spectrum of cotton fabric treated with VBL-CDs under ultraviolet irradiation, and c is the peak statistical curve of figures a and b.
[0034] Figure 6 Figures a and b are the antibacterial effect and inhibition rate comparison of VBL-CDs aqueous solutions with different concentrations on Staphylococcus aureus and Escherichia coli.
[0035] Figure 7 This is a comparison of the antibacterial rates of VBL-CDs, VBL and different carbon dot materials against Staphylococcus aureus and Escherichia coli.
[0036] Figure 8 Figures a and b are the antibacterial effect and inhibition rate comparison of cotton fabrics treated with different amounts of VBL-CDs against Staphylococcus aureus and Escherichia coli.
[0037] Fig. 9 Cell viability of NIH / 3T3 cells treated with different fabric samples.
[0038] Fig.10 The survival rate of NIH / 3T3 cells after ultraviolet irradiation under different conditions. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. The replacement of simple parameters in the implementation mode cannot be repeated one by one in the examples, but the present invention is not limited thereto. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be regarded as equivalent replacement methods and should be included in the scope of the present invention.
[0040] The materials used in the following examples are all commercially available products.
[0041] Example 1
[0042] The carbon dot material VBL-CDs of the present invention is synthesized by the following steps:
[0043] (1) 300 mg of fluorescent whitening agent VBL, 800 mg of citric acid and 100 mg of copper chloride, as well as 2.5 mL of ammonia water, 2.5 mL of ultrapure water and 50 μL of ethylenediamine were put into a 50 mL polytetrafluoroethylene reactor, heated to 190 ° C, and reacted for 3 h;
[0044] (2) After the system is cooled to room temperature, 5 mL of ultrapure water is added to the dark brown solution obtained by the reaction, and ultrasonic treatment is performed for 30 min. The solution obtained after ultrasonic treatment is then dialyzed for 4 h using a dialysis bag with a molecular weight cutoff of 1000 Da. The ultrapure water is replaced every 2 h during the dialysis process to obtain a purified VBL-CDs solution, which is then freeze-dried to obtain a green VBL-CDs solid powder.
[0045] Example 2
[0046] The carbon dot material VBL-CDs of the present invention is synthesized by the following steps:
[0047] (1) 300 mg of fluorescent whitening agent VBL, 800 mg of citric acid and 100 mg of copper chloride, as well as 2.5 mL of ammonia water, 2.5 mL of ultrapure water and 50 μL of ethylenediamine were put into a 50 mL polytetrafluoroethylene reactor, heated to 190 ° C, and reacted for 5 hours;
[0048] (2) After the system is cooled to room temperature, 5 mL of ultrapure water is added to the dark brown solution obtained by the reaction, and ultrasonic treatment is performed for 30 min. The solution obtained after ultrasonic treatment is then dialyzed for 4 h using a dialysis bag with a molecular weight cutoff of 1000 Da. The ultrapure water is replaced every 2 h during the dialysis process to obtain a purified VBL-CDs solution, which is then freeze-dried to obtain a green VBL-CDs solid powder.
[0049] Example 3
[0050] The carbon dot material VBL-CDs of the present invention is synthesized by the following steps:
[0051] (1) 250 mg of fluorescent whitening agent VBL, 850 mg of citric acid and 100 mg of copper chloride, as well as 2.4 mL of ammonia water, 2.6 mL of ultrapure water and 50 μL of ethylenediamine were put into a 50 mL polytetrafluoroethylene reactor, heated to 180 ° C, and reacted for 4 h;
[0052] (2) After the system is cooled to room temperature, 6 mL of ultrapure water is added to the dark brown solution obtained by the reaction, and ultrasonic treatment is performed for 30 min. The solution obtained after ultrasonic treatment is then dialyzed for 4 h using a dialysis bag with a molecular weight cutoff of 1000 Da. The ultrapure water is replaced every 2 h during the dialysis process to obtain a purified VBL-CDs solution, which is then freeze-dried to obtain a green VBL-CDs solid powder.
[0053] Example 4
[0054] The carbon dot material VBL-CDs of the present invention is synthesized by the following steps:
[0055] (1) 300 mg of fluorescent whitening agent VBL, 800 mg of citric acid and 100 mg of copper chloride, as well as 2.5 mL of ammonia water, 2.5 mL of ultrapure water and 50 μL of ethylenediamine were put into a 50 mL polytetrafluoroethylene reactor, heated to 190 ° C, and reacted for 4 hours;
[0056] (2) After the system is cooled to room temperature, 5 mL of ultrapure water is added to the dark brown solution obtained by the reaction, and ultrasonic treatment is performed for 30 min. The solution obtained after ultrasonic treatment is then dialyzed for 5 h using a dialysis bag with a molecular weight cutoff of 500 Da. The ultrapure water is replaced every 1.5 h during the dialysis process to obtain a purified VBL-CDs solution, which is then freeze-dried to obtain a green VBL-CDs solid powder.
[0057] Example 5
[0058] 1) Verify the fluorescence properties of VBL-CDs
[0059] like Figure 1 As shown in a and b, the UV-visible absorption spectrum of 0.1 mg / mL VBL-CDs aqueous solution tested by Mepto UV6100 spectrophotometer has a maximum absorption at 340 nm. At the same time, the analysis by Hitachi FL-7000 fluorescence spectrometer shows that the optimal excitation wavelength of VBL-CDs (0.1 mg / mL) is 380 nm and the emission center is 440 nm, which is very similar to the fluorescence spectrum of VBL and meets the requirements as a fluorescent whitening agent. Figure 1 Figure c is the PL spectrum of VBL-CDs under different excitation wavelengths. It can be seen from the figure that when the excitation wavelength increases from 305nm to 395nm, VBL-CDs presents a single emission center and has non-excitation-dependent characteristics.
[0060] like Figure 2 As shown, under the same concentration conditions (0.1 mg / mL), the fluorescence intensity of VBL-CDs was significantly stronger than that of VBL.
[0061] 2) Testing the fluorescence stability of VBL-CDs
[0062] from Figure 3As can be seen from figures a and b, the fluorescence intensity of the VBL-CDs aqueous solution (0.1 mg / mL) did not decrease significantly after being irradiated under 365 nm ultraviolet light for 35 min, indicating that the prepared VBL-CDs have good resistance to photobleaching. However, under the same conditions, the fluorescence intensity of the VBL aqueous solution (0.1 mg / mL) was greatly reduced, only 4.7% of the original (0 min).
[0063] The fluorescence lifetimes of VBL-CDs and VBLs were further compared, as shown in Figure 3 As shown in c, the lifetime of VBL-CDs is significantly longer than that of VBL. When VBL is converted into carbon dot material VBL-CDs, the average lifetime increases from 3.65ns to 13.17ns, so the VBL-CDs of the present invention are expected to replace the fluorescent whitening agent VBL and be promoted and applied to different fields.
[0064] Example 6 Whitening and brightening effect of VBL-CDs on cotton fabric
[0065] The same cotton fabric sample (4g) was immersed in 200mL (about 200g) of VBL-CDs solution with concentrations of 0.05mg / mL, 0.1mg / mL, 0.15mg / mL, and 0.2mg / mL, respectively. The amount of VBL-CDs was 0.25%, 0.5%, 0.75%, and 1% (owf), respectively. Stirred at room temperature for 1h, the sample was taken out and rinsed in cold water, and then dried overnight at room temperature. The whiteness index (WI) of the cotton fabric samples treated with different amounts of VBL-CDs was measured using a colorimeter to evaluate the optical whitening effect.
[0066] According to the above method, the whiteness index (WI) of cotton fabric samples treated with different amounts of VBL and CDs (the synthesis steps of CDs and VBL-CDs in Example 1 are the same, but VBL is not used as a precursor) was measured for comparison.
[0067] like Figure 4 As shown, when the dosage is 0.25% and 0.5%, the whiteness of the cotton fabric treated with VBL and VBL-CDs is significantly improved compared with the untreated cotton fabric (Ctrl group) and the cotton fabric treated with CDs, and it can be seen that the whitening effect of VBL-CDs is comparable to that of VBL.
[0068] At the same time, cotton fabrics treated with VBL-CDs have better light stability than cotton fabrics treated with VBL and are more resistant to UV irradiation. Figure 5 As shown, in other words, the cotton fabric treated with VBL-CDs has a more lasting whitening and brightening effect.
[0069] Example 7 Testing the Antibacterial Activity of VBL-CDs
[0070] In this example, Gram-negative Escherichia coli (E. coli, ATCC 29213) and Gram-positive Staphylococcus aureus (S. aureus, ATCC 25922) were used; the single colonies of the two bacteria cultured on solid culture medium were transferred to a shaking flask filled with LB liquid culture medium and cultured in a constant temperature shaking incubator (37°C, 160 rpm). After culturing for 12 hours, the bacterial solution was taken out and diluted to 10 6 CFU / mL, for future use.
[0071] In bacterial counting, the diluted bacterial solution (10 6 CFU / mL) were cultured with different concentrations of VBL-CDs aqueous solution (25μg / mL, 50μg / mL, 100μg / mL, 200μg / mL) and VBL aqueous solution (200μg / mL); after incubation at 37°C for 1h, each sample was serially diluted with sterile PBS (pH=7.4), and then plate counts were performed; then the inhibition rate / antibacterial rate was calculated: inhibition rate / antibacterial rate = (number of colonies in the control group - number of colonies in the treatment group) / number of colonies in the control group × 100%, the results are shown in Figure 6 (The control group refers to the direct culture of the diluted bacterial solution, Figure 6 Ctrl group in the .
[0072] Figure 6 The results showed that VBL-CDs had excellent antibacterial activity against Escherichia coli and Staphylococcus aureus at concentrations of 100 μg / mL and 200 μg / mL, while VBL had no antibacterial activity even at a concentration of 200 μg / mL.
[0073] Example 8 Testing the antibacterial effect of cotton fabric loaded with VBL-CDs (VBL-CDs / cotton)
[0074] In this example, Gram-negative Escherichia coli (E. coli, ATCC 29213) and Gram-positive Staphylococcus aureus (S. aureus, ATCC 25922) were used to test the antibacterial effect; the cotton fabric used in the experiment was 4 g of cotton cloth.
[0075] First, the two bacterial colonies cultured on solid culture medium were transferred to a shake flask containing LB liquid culture medium and cultured in a constant temperature shaker (37°C, 160 rpm). After culturing for 12 hours, the bacterial solution was taken out and diluted to 10 6 CFU / mL, which was used for subsequent experiments.
[0076] Experiment 1: Comparison of the antibacterial effects of VBL-CDs, VBL and different carbon dot materials
[0077] The experiments against Staphylococcus aureus and Escherichia coli were divided into 5 groups:
[0078] (1) Ctrl group: cotton cloth without any treatment;
[0079] (2) VBL group: cotton cloth (4 g) was soaked in 200 mL of 0.1 mg / mL VBL aqueous solution, corresponding to a VBL dosage of 0.5% (owf), rinsed and air-dried after 1 h, and cut into 4 cm × 2.5 cm for subsequent experiments;
[0080] (3) CDs (VBL / CA / CuCl2) group: The cotton cloth was treated with the VBL-CDs aqueous solution synthesized in Example 1, and the treatment conditions were the same as those of the VBL group;
[0081] (4) CDs (CA / CuCl2) group: The carbon dot material was synthesized by the same steps as in Example 1, except that VBL was not used as a precursor. The cotton cloth was then treated with the carbon dot material solution under the same treatment conditions as the VBL group.
[0082] (5) CDs (VBL / CA) group: The carbon dot material was synthesized by the same steps as in Example 1, except that CuCl2 was not used as a precursor. The cotton cloth was then treated with the carbon dot material solution under the same treatment conditions as the VBL group.
[0083] The cotton samples of the above groups were added to a 6-well plate, and 500 μL of Staphylococcus aureus and Escherichia coli were added to each well, respectively, and incubated at 37°C for 6 hours; after incubation, the cotton samples were removed and thoroughly vortexed for 2 minutes with 2 mL of Hank's balanced salt solution (HBSS buffer) to completely elute the bacteria in the samples; then the bacterial suspension of each group was diluted 1000 times and evenly spread on the LB agar plate; after incubation, the number of microbial colonies was counted and the inhibition rate was calculated. The results are shown in Figure 7 .
[0084] like Figure 7 As shown, VBL-CDs have good antibacterial effect, and its antibacterial activity is significantly greater than that of cotton cloth without any treatment and cotton cloth treated with VBL; this indicates that VBL-CDs not only improves the whiteness of the fabric, but also gives the fabric antibacterial function, realizing its multifunctional application.
[0085] Furthermore, from Figure 7 The results show that only the CDs (VBL / CA / CuCl2) group can effectively inhibit the growth of Staphylococcus aureus and Escherichia coli at the same time, that is, it has antibacterial function against both Gram-positive and Gram-negative bacteria; this indicates that the antibacterial function of the VBL-CDs of the present invention is achieved through the synergistic effect of VBL, CA, and CuCl2 as its synthetic precursors.
[0086] Experiment 2: Comparison of the antibacterial effects of different dosages of VBL-CDs
[0087] The specific operation is as follows: 200mL of 0.05mg / mL, 0.1mg / mL, 0.15mg / mL, and 0.2mg / mL VBL-CDs solutions were used to treat cotton samples, and the corresponding VBL-CDs dosages were 0.25%, 0.5%, 0.75%, and 1% (owf), respectively; then, 500μL of Staphylococcus aureus and Escherichia coli bacterial solutions were added to the cotton samples of each group, and incubated at 37°C for 6h; after the incubation, the bacteria were transferred from the fabric to 2mL of phosphate buffer by vortexing, and then 100μL of the mixed system was inoculated onto the agar plate according to the dilution coating plate method, and after evenly spreading, it was placed in a constant temperature incubator (37°C), and the plate was inverted to prevent contamination; after 18h, the culture dish was photographed, and the bacterial growth on each agar plate was recorded, and finally the antibacterial rate was obtained by counting the number of colonies.
[0088] like Figure 8 As shown in a and b, different dosages of VBL-CDs can effectively kill Staphylococcus aureus and Escherichia coli, among which 0.5% (owf) VBL-CDs has the best antibacterial effect, with the inhibition rates against Staphylococcus aureus and Escherichia coli reaching 98% and 99%, respectively.
[0089] Example 9 Testing the biocompatibility and UV protection properties of VBL-CDs
[0090] 1) Biocompatibility of VBL-CDs
[0091] The cytotoxicity of VBL-CDs was studied using NIH / 3T3 fibroblasts.
[0092] NIH / 3T3 cells were seeded into 96-well plates at a density of 5000 cells / well and cultured for 24 h until the cells attached to the wall. Then, cotton fabrics (0.5×0.5 cm 2 ) were added to a 96-well plate (one piece per well) and co-cultured with NIH / 3T3 cells for 24 h; then, 10 μL of CCK-8 solution was added to the culture medium and incubated for 1.5 h; the absorbance of the sample was detected at a wavelength of 450 nm using an ELISA reader (Tecan, infinite F50, Switzerland).
[0093] Fig. 9 The results showed that the cell survival rates on cotton fabrics treated with VBL-CDs and VBL were comparable to those on untreated cotton fabrics (Ctrl group) (no significant difference), and the cell survival rates of both groups exceeded 90%, indicating good cell compatibility.
[0094] 2) UV protection performance
[0095] The protective effect of cotton fabric treated with VBL-CDs against skin UV damage was further studied using the CCK-8 test.
[0096] NIH / 3T3 cells were seeded into 6-well plates at a density of 40,000 cells / well, cultured for 24 h, and then covered with aluminum film (control group), untreated cotton fabric (blank group), cotton fabric treated with 0.5% (owf) VBL (VBL group), and cotton fabric treated with 0.5% (owf) VBL-CDs (VBL-CDs group). The group without protection was called the UV group; then, the cells were irradiated with ultraviolet light at a wavelength of 254 nm for 1 h; after further culture for 1 day, the viability of NIH / 3T3 cells was evaluated by CCK-8 assay.
[0097] Fig.10 The results showed that the VBL group and VBL-CDs group provided satisfactory UV protection, with cell viability rates of 95.5% and 94.1%, respectively, while about 20% of cells died in the unprotected (UV) group after UV irradiation.
Claims
1. A carbon dot material with both whitening and antibacterial functions, characterized in that: It is synthesized by hydrothermal method with fluorescent brightener VBL, citric acid, cupric chloride, ammonia water, ethylenediamine and water as raw materials.
2. The carbon dot material with both whitening and antibacterial functions according to claim 1, characterized in that: The mass ratio of the solid raw material fluorescent brightener VBL, citric acid and cupric chloride is 2-3:7-9:
1.
3. The carbon dot material with both whitening and antibacterial functions according to claim 2, characterized in that: The volume ratio of the liquid raw materials ammonia water, ethylenediamine and water is 45-55:45-55:1; the ratio of the solid raw material to the liquid raw material is 230-260 mg:1 mL.
4. The carbon dot material with both whitening and antibacterial functions according to claim 3, characterized in that: The reaction temperature of the hydrothermal method is 180-200° C., and the reaction time is 2-5 hours.
5. The carbon dot material with both whitening and antibacterial functions according to claim 4, characterized in that: The product synthesized by the hydrothermal method is post-treated; the post-treatment steps are: adding ultrapure water to the product synthesized by the hydrothermal method, and ultrasonicating for 30 minutes; dialysis purification of the solution obtained after ultrasonication, and then freeze-drying to obtain the carbon dot material.
6. The carbon dot material with both whitening and antibacterial functions according to claim 5, characterized in that: The dialysis purification is to use a dialysis bag with a molecular weight cutoff of 500 to 3000 Da and ultrapure water to dialyze the solution obtained after ultrasound for 4 to 10 hours, and the ultrapure water is replaced every 1 to 3 hours during the dialysis process.
7. A fluorescent whitening agent comprising the carbon dot material according to claim 1.
8. Use of the carbon dot material according to claim 1 or the fluorescent whitening agent according to claim 7 in the preparation of a fabric detergent with whitening and brightening effects or a fabric care agent with whitening and brightening effects.
9. Use of the carbon dot material according to claim 1 or the fluorescent whitening agent according to claim 7 in the preparation of an antibacterial fabric detergent or an antibacterial fabric care agent.
10. The use according to claim 8 or 9, characterized in that: The amount of the carbon dot material is 0.25-1.0%.
Citation Information
Patent Citations
Fluorescein carbon dot dyeing reagent for fungus detection, dyeing method and application
CN113943572A
Preparation method of metal-doped fluorescent biomass carbon quantum dots
CN114214068A
Preparation method and application of antibacterial carbon dot compound
CN116850299A
Monatomic copper-doped near-infrared carbon dots as well as preparation method and application thereof
CN118146794A
Copper ion doped carbon dots, preparation and application thereof as photosensitizer for photodynamic therapy
WO2020172917A1
